Practical microwave circuits - Maas, Stephen A. (Artech House, 2014)
This book differentiates itself by presenting microwave and RF technology from a circuit design viewpoint, rather than a set of electromagnetic problems. The emphasis is on gaining a practical understanding of often overlooked but vital physical processes.